2019
DOI: 10.1002/ijfe.1788
|View full text |Cite
|
Sign up to set email alerts
|

Managerial entrenchment, financial constraints, and investment choice in unlisted firms

Abstract: This paper examines how internally generated cash is allocated for investment in unlisted firms in the post‐global financial crisis period. We estimate models using a panel data set from unlisted firms in the United Kingdom from 2009 to 2014. With the use of a commercially available credit rating and a widely used index in the literature to proxy for external financial constraints, the paper concludes that less financially constrained firms display a higher investment‐cash flow sensitivity. This association ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…We also observed that tangibility ( TAN ) and leverage ( BLev ) are positively and significantly related at the 1% level. This underscores the importance of asset base as an added security in reducing a lender's risk (Danso & Adomako, 2014; De Jong et al, 2008; Nicodano & Regis, 2019; Ranasinghe, 2019; Williamson, 1988). This tends to support both the pecking order and the trade‐off theories.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…We also observed that tangibility ( TAN ) and leverage ( BLev ) are positively and significantly related at the 1% level. This underscores the importance of asset base as an added security in reducing a lender's risk (Danso & Adomako, 2014; De Jong et al, 2008; Nicodano & Regis, 2019; Ranasinghe, 2019; Williamson, 1988). This tends to support both the pecking order and the trade‐off theories.…”
Section: Resultsmentioning
confidence: 93%
“…Following this, a review of the capital structure literature identifies various theories that that have been at the forefront of the debate on how various firm‐level characteristics affect firms' debt‐equity choice decisions (Frank & Shen, 2019; Grosse‐Rueschkamp et al, 2019). For example, arising out of discussion of the irrelevance theory is the trade‐off theory, which argues that an optimal capital structure is determined by the costs and benefits associated with the use of debt as against equity (Nicodano & Regis, 2019; Ranasinghe, 2019). Thus, there is either an optimal debt‐equity ratio, or a range for this ratio, whereby a firm's average cost of capital can be minimised (Bartholdy, Mateus, & Olson, 2015; Brown, Dutordoir, Veld, & Veld‐Merkoulova, 2019; Scott, 1977).…”
Section: Literature Review: Theory and Empiricsmentioning
confidence: 99%
See 3 more Smart Citations